TRANSDUCERS 2009 - 2009 International Solid-State Sensors, Actuators and Microsystems Conference 2009
DOI: 10.1109/sensor.2009.5285721
|View full text |Cite
|
Sign up to set email alerts
|

An organic electronic ion pump to regulate intracellular signaling at high spatiotemporal resolution

Abstract: Current technologies for cell stimulation suffer from a variety of drawbacks. Indeed, precise, localized, and minimally disruptive machine-to-cell interfacing is difficult to achieve. Here we present the organic electronic ion pump (OEIP), a polymer-based delivery system exhibiting high spatial, temporal, and dosage precision. Based on electrophoretic transport of positively charged species, the OEIP can deliver -with high precision -an array of biologically relevant substances without fluid flow, thus elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…For these reasons, organic semiconductors have lately been used for a broad spectrum of bioelectronics applications. For example, to more directly sense and monitor relevant physiological parameters and convert them to electronic signals [12], or conversely, to regulate (actuate) the physiology of cells and tissues with high spatiotemporal resolution [13]. In addition, organic semiconductors have the advantage of mechanical flexibility, the softness required for biotic interfaces, and ease of processing.…”
Section: Organic Bioelectronics and Iontronicsmentioning
confidence: 99%
See 2 more Smart Citations
“…For these reasons, organic semiconductors have lately been used for a broad spectrum of bioelectronics applications. For example, to more directly sense and monitor relevant physiological parameters and convert them to electronic signals [12], or conversely, to regulate (actuate) the physiology of cells and tissues with high spatiotemporal resolution [13]. In addition, organic semiconductors have the advantage of mechanical flexibility, the softness required for biotic interfaces, and ease of processing.…”
Section: Organic Bioelectronics and Iontronicsmentioning
confidence: 99%
“…Iontronic devices have mainly two components, electrodes and IEM, of which the IEM can be considered as the heart of these devices [31]. Several IEMs have been successfully used in various iontronic components and there has been tremendous growth in the field of IEMs for iontonic devices from linear IEM materials that show excellent conducting properties for smaller ions like Na + , K + , Ca 2+ , Cl -, and Iand biomoelecules less than 200 g/mol like GABA + , acetylcholine (Ach + ), and salicylic acid (SA -), to tailor-made IEM materials such as hyperbranched polyglycerol that has shown excellent proven transport properties for larger ions like indigo carmine (466 g/mol) and methylene blue (320 g/mol) [13,[32][33][34][35]. The most widely used ion transport membrane for the first generation OEIPS was over-oxidized PE-DOT:PSS acting as a CEM (see section 5.1.3.1).…”
Section: Towards Iontronic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the tools that could be used for organ specific delivery of effective compounds to plants are organic electronic ion pumps (OEIPs), a polymer-based delivery system and organic electrochemical transistor (OECT) (Simon et al, 2009a ; Nielsen et al, 2016 ). They can deliver with high precision and efficiency a range of biologically relevant substances.…”
Section: Sensing Devices—on the Way To Biohybridmentioning
confidence: 99%
“…They can deliver with high precision and efficiency a range of biologically relevant substances. Ion transport was shown to be able to mimic, and to precisely affect Ca 2+ signaling in a programmed way (Simon et al, 2009a , b ). It was demonstrated that OEIPs can be used as programmable “machine-to-brain” (or “machine-to-cell”) communication platform.…”
Section: Sensing Devices—on the Way To Biohybridmentioning
confidence: 99%